Adherence to secondary antibiotic prophylaxis among patients with acute rheumatic fever and/or rheumatic heart disease: a systematic review and meta-analysis - Melaku Bimerew; Freweyni Gebreegziabher Araya; Manay Ayalneh (BMJ Open)
Objectives Worldwide, a number of studies have been conducted to assess the prevalence of adherence to secondary antibiotic prophylaxis and to identify the associated factors (reasons) for poor adherence among patients with rheumatic heart disease or acute rheumatic fever (RHD/ARF). However, results were highly inconsistent with a prevalence ranging from 10% to 93%; and the reported reasons or associated factors have not been systematically reviewed. Therefore, this study aimed to assess the prevalence of adherence to secondary antibiotic prophylaxis among patients with RHD/ARF; and to review the associated factors (reasons) for poor adherence.Design Systematic review and meta-analysis.Data sources PubMed/Medline, Google Scholar, Cochrane Review and African Journals Online databases.Eligibility criteria Articles published in English from 1 January 2005 to 1 December 2022 and reported the prevalence of adherence using ≥80% cut-off points were included.Data extraction and synthesis Data were extracted using the Microsoft Excel and analysed by STATA V.11.0. A meta-analysis was conducted using the weighted inverse-variance random-effects model. Reasons for poor adherence were identified through thematic analysis.Results 33 articles with a total sample size of 7158 patients were included. The pooled prevalence of adherence to secondary antibiotic prophylaxis among patients with RHD/ARF was found to be 58.5% (95% CI: 48.2% to 68.7%; I2=99.2%; p<0.001). Rural residency, lack of money, distance from the health institutions, inaccessibility, poor counselling, forgetting schedules, lack of disease knowledge and fear of injection pain were the reported factors or reasons for poor adherence.Conclusion About 41.5% of patients with RHD/ARF were found to have poor adherence. Long distance from health institutions, forgetting schedules, poor counselling and lack of knowledge and skill among healthcare workers were some of the modifiable reasons for poor adherence. Therefore, decentralisation of the follow-up care, creating schedule reminding systems and providing targeted health education might help to improve adherence.